THE DEVELOPMENT OF LEARNING ACTIVITIES SKILLS ACCORDING TO DAVID'S CONCEPT IN BASIC DANCING ART FOR 5TH GRADE PRIMARY SCHOOL STUDENTS - Mapatang, Warayut; Pharanat, Wanida; Chantachum, Natthachai (Journal of MCU Nakhondhat, 2020)
The objective of this research are: 1) To develop learning activities skills according to David's concept in basic dancing art for Primary school in 5th grade to have an efficiency based on the criteria of 80/80. 2) To learn the effectiveness index of learning activities skills according to David's concept in basic dancing act for Primary school in 5th grade 3) To learn the skill after learning the activities skills according to David's concept in basic dancing art for Primary​ school​ in​ 5th​ grade. The group sample we used in this research is the Primary school students in 5th grade, room 1, second semester of 2019 at Ban Hai Sa-at school, Khao Suan Kwang district, Primary Educational Service area, Khonkaen district 4, 106 sample students. The random group sample we used is the Cluster Random Sampling. The tools we used to gather data informations are 6 learning activities plans according to David's concept in basic dancing​ art​, the suitability the educational achievement tests, the confidence level and the measurement skills in Rubric Score 5 levels. The statistic we used to analyze the information are percentage, the average mean and the standard deviation. The research results show that: 1) The efficiency level of learning activities skills plans according to David's concept for 5th grade students in basic dancing art is increasingly to 87.08/82.58 which is higher than the standard criteria of 80/80. 2) The effectiveness index of learning activities skills according to David's concept in basic dancing act for Primary school in 5th grade is equal to 0.7191 3) After the Primary​ school in 5th grade students learned the activities skills according to David's concept in basic dancing art, the overall results in the percentage is 84.04